Effect of Modified Atmospheres on Quality and Chilling Injury of ’Nam Dok Mai’ Mango Fruits - Manoch Koolpluksee; Saichol Ketsa; Suranant Subhadrabandhu (Agriculture and Natural Resources, 1993)
’Nam Dok Mai’ mango fruits at the age of 95-100 days after full bloom were kept in polyethylene (PE, 31 µ thickness) and polypropylene (PP, 39 µ thickness) bags with the size of 12" x 17" and had 0 and 8 pinholes with and without ethylene absorbent (EA). Fruits were stored at 10°C with 90-93% RH. Fruits kept in 8 pinholes PP bags with and without EA had the longest storage life of 21 and 23 days, respectively, while fruits in plastic baskets (control) had less than 5 days of storage life. Eight pinholes PP bags with and without EA had 12.38 - 14.94% CO2 and 8.91 - 10.72% O2 during storage period. These storage conditions reduced off-odor, off-flavor and chilling injury (CI) and delayed ripening of fruits. CO2 injury and CI were increased depending on storage period. EA inside the PP apparently did not influence Cl and storage life. Fruits with CI showed brown-grayish skin brown pulp and dark brown endocarp, while seed coat and cotyledon were dark in color. CO2 injury showed only in PP bags without perforation whereas slight CI showed in all 8 pinholes PE and PP bags with and without EA.